Prambors Radio's Communication Strategy for Sustaining Relevance in the Digital Era - Rahmasari, Mila Annisa; Magvira Yuliani; Yulia Rahmawati (Golden Ratio of Social Science and Education, 2025)
This study aims to examine the communication strategies implemented by Radio Prambors to maintain its existence amidst the flow of media digitalization. A qualitative case study approach was used, supported by media convergence theory. This study describes how Radio Prambors adopts new media to expand its audience reach, while meeting the needs and motivations of listeners. The study results show that Radio Prambors implements various communication strategies such as social media integration, diversification of broadcast content, two-way interaction with listeners, and optimization of digital platforms to strengthen audience engagement. This study confirms that the success of radio in the digital era is highly dependent on the ability to adapt through technological innovation, responsive broadcast management, and a participatory approach to the audience.